Phylogenetic Insights into the Functional Relationship between Primate Lentiviral Reverse Transcriptase and Accessory Proteins Vpx/Vpr - Sakai, Yosuke; Doi, Naoya; Miyazaki, Yasuyuki; Adachi, Akio; Nomaguchi, Masako (Frontiers in Microbiology, 2016)
The efficiency of reverse transcription to synthesize viral DNA in infected cells greatly influences replication kinetics of retroviruses. However, viral replication in non-dividing cells such as resting T cells and terminally differentiated macrophages is potently and kinetically restricted by a host antiviral factor designated SAMHD1 (sterile alpha motif and HD-domain containing protein 1). SAMHD1 reduces cellular deoxynucleoside triphosphate (dNTP) pools and affects viral reverse transcription step. Human immunodeficiency virus type 2 (HIV-2) and some simian immunodeficiency viruses (SIVs) have Vpx or Vpr to efficiently degrade SAMHD1. Interestingly, the reverse transcriptase (RT) derived from HIV-1 that encodes no anti-SAMHD1 proteins has been previously demonstrated to uniquely exhibit a high enzymatic activity. It is thus not irrational to assume that some viruses may have acquired or lost the specific RT property to better adapt themselves to the low dNTP environments confronted in non-dividing cells. This adaptation process may probably be correlated with the SAMHD1-antagonizing ability by viruses. In this report, we asked whether such adaptive events can be inferable from Vpx/Vpr and RT phylogenetic trees overlaid with SAMHD1-degrading capacity of Vpx/Vpr and with kinetic characteristics of RT. Resultant two trees showed substantially similar clustering patterns, and therefore suggested that the properties of RT and Vpx/Vpr can be linked. In other words, HIV/SIVs may possess their own RT proteins to adequately react to various dNTP circumstances in target cells.